PENGEMBANGAN SOAL LITERASI NUMERASI MENGGUNAKAN KONTEKS SOSIAL-BUDAYA LABUHANBATU - Retno Ayu Trisnawati; Fajriana; Herizal (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Assessment Kompetisi Minimum (AKM) is an assessment of the basic competencies possessed by students on a national scale. One of the skills required to participate in the AKM is numeracy literacy. To train these abilities, students must get used to working on numeracy literacy questions. However, at SMP Negeri 2 Rantau Selatan which is located in Labuhanbatu, the treasury of numeracy literacy questions is still lacking and those that use the socio-cultural context of Labuhanbatu do not yet exist. So it is necessary to develop numeracy literacy questions using the socio-cultural context of Labuhanbatu. The purpose of this study was to determine the validity of the results of developing numeracy literacy questions using the socio-cultural context of Labuhanbatu and to determine the numeracy literacy skills of students using these questions. The questions referred to the Minimum Competition Assessment (AKM). The type of this research is Design Research type Development Study which has been modified. This research consists of a stage preliminary, self-evaluation, expert review, and field test. Based on the validation from the validator, all questions can be used for field tests. The results of the field test consist of 14 questions with the criteria "very adequate for use", 2 questions with the criteria "adequate for use", and 1 question with the criteria "considered for use". All questions are included in the final product. The final product is used to see the students' numeracy literacy skills. The percentage of students' numeracy literacy skills is 3% "high" and 97% "low". The average percentage of students who answer questions at the cognitive level of knowing, applying, and reasoning are 50% and 32%, respectively. and 18%.